A study of the top-cited studies on drug therapy for HIV - Tang, Jie; Yuan, Yanwen; Sun, Lei; Wu, Bo; Yu, Lin (Frontiers in Pharmacology, 2022)
Background Research on drug therapy for HIV remained major hot-spots, but relevant data were not satisfactory. We aimed to assess the status and trends of the most cited studies on drug therapy for HIV by using bibliometric methods. Methods The Web of Science Core Collection database was searched for the drug therapy for HIV studies. The period for retrieval was from the beginning of the database to July 26, 2022. The 100 top cited studies were selected. These general information and bibliometric data were collected and analyzed. VOS viewer software was used for visualization analysis. Results The number of citations for the 100 top cited studies ranged from 451 to 5597 and were published from 1987 to 2017. These studies were published in 29 journals. The top 3 journals in terms of the number of studies were the New England Journal of Medicine (n = 22), Lancet (n = 15), and JAMA (n = 13). The most frequently nominated author was Matthias Eiger from the University of Bern, who has contributed 5 studies. United States, Switzerland, and England contributed most of the highly cited studies. Research hot spots reflected clinical trials, treatment adverse events, basic research, and clinical adherence. Conclusion The majority of 100 top-cited studies have been published in the United States, and primarily focused on treatment adverse events, basic research, and clinical adherence. They provide a basic list of the most important and influential academic contributions to literature of HIV drug treatment for researchers.